Menelaah Struktur Mood dan Residu dalam Pidato Berbahasa Arab Anis Matta tentang Palestina dan Implikasi Pedagogis terhadap Pemahaman Membaca Kritis - Nunung, Nunung; Supriadi, Rinaldi (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2026)
The Palestinian-Israeli conflict has become a global issue that has generated diverse diplomatic and rhetorical responses from various countries, including Indonesia, which consistently supports Palestinian independence. This study aims to describe the Mood and Residue structures in Anis Matta's Arabic speech at the Extraordinary Meeting of the Foreign Ministers of the Organisation of Islamic Cooperation (OIC) in Riyadh, and to explain their implications for the development of critical Arabic reading comprehension. This study employs a qualitative descriptive approach with document analysis techniques applied to 53 clauses in the speech text. The analysis focuses on identifying Subjek and Finite as constituents of Mood, and Predicator, Complement, and Adjunct as constituents of Residue within the Systemic Functional Linguistics (SFL) framework. The findings reveal that Subjek and Predicator dominate the Mood and Residue structure, indicating that the speech is constructed through affirmation of social actors and representation of collective action as strategies for building solidarity and legitimacy. These findings confirm that Mood and Residue structures function as interpersonal devices in diplomatic discourse. Pedagogically, this analysis can be utilized to support critical Arabic reading instruction through understanding social relations and ideological positioning in texts